Analisis Kesalahan Siswa dalam Menyelesaikan Soal Perpangkatan dan Bentuk Akar Berdasarkan Kriteria Watson Ditinjau dari Perbedaan Gender - Usman Mulbar; Nasrullah; Yulinar (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2022)
This study aims to determine: (1) the types of errors, (2) the level of error categories, and (3) the causes of students making mistakes in solving problems of rank and root form based on Watson's criteria in terms of gender differences. The type of research used is descriptive research with a qualitative approach. There are six research subjects, namely three male students and three female students. The instruments used in data collection were test instruments and interview guidelines. The results showed that male students tended to make errors in the response level conflict with a fairly high error category where students had tried to solve the problem but students did not understand the concept of working on the problem so they failed to get the right conclusion. In addition, students only write the final answer without being accompanied by a clear reason or step for solving it because students do not know the right way to work on the problem. Meanwhile, female students tend to make mistakes in the skill hierarchy problem with the small error category where students lack the skills to calculate some arithmetic operations contained in the problem solving step and tend make mistakes other than the seven Watson categories with the small error category where students do not answer questions because students do not know the steps. solution that must be used in the work because students rarely work on problems with different forms.